Active‐Layer Thickness Measurements Using a Handheld Penetrometer at Boreal and Tundra Sites in Eastern Siberia. (26th July 2016) - Iijima, Yoshihiro; Park, Hotaek; Konstantinov, Pavel Ya.; Pudov, Grigory G.; Fedorov, Alexander N.
Abstract: Active‐layer thickness (ALT) is one of the most robust measures used to assess the impact of climate change on terrestrial permafrost. Testing of a handheld dynamic cone penetrometer showed that it was capable of measuring ALT with the same level of accuracy as conventional methods in boreal and tundra sites in eastern Siberia. The penetrometer also characterised the vertical structure of ground hardness within the active layer. The vertical profile of penetrometer measurements corresponded closely with soil plasticity and the liquid limit in high‐centred polygons produced by thermokarst subsidence in dry grassland areas at a boreal site at Churapcha. The ALT was markedly deeper (>70 cm) at gravelly slope points adjacent to a wet tundra plain (<50 cm) in a CALM grid (R8) at Tiksi. Overall, the penetrometer is considered to provide an accurate and informative proxy for rapidly assessing the spatial heterogeneity and interannual changes in ALT. Copyright © 2016 John Wiley & Sons, Ltd.